Delineamento de critérios para triagem de casos do setor pré-processual no Brasil - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
The successful implementation of the National Judicial Public Policy on the Adequate Treatment of Conflicts of Interest requires the adoption of effective procedures. The general objective of the dissertativo was to develop a guide for screening cases for the pre-procedural sector in Brazilian judicial centers, using the criteria outlined to parameterize the choice of consensual mechanisms. The specific objectives include characterizing the judicial centers for conflict resolution and citizenship within the scope of the National Judicial Public Policy for the Adequate Treatment of Conflicts of Interest; identify the composition of the Conflict Resolution System; parameterize the selection criteria for consensual mechanisms for screening cases in the pre-procedural sector and develop the case screening guide. This is a Translational Research applied to Law, which followed deductive precepts and used qualitative analysis of data and indicators. Literature review, document analysis, questionnaire application and product development were used. The pre-procedural sector of the Judicial Center for Conflict Resolution and Citizenship of Ponta Grossa/PR (CEJUSC-PRÉ/PG) was defined as the research locus and the year 2022 was defined as the time frame. Data were collected in 336 pre- procedural procedures, through PROJUDI, and together with the 12 members of the agency's screening team, in 2023. The study characterized and identified the elements that make up the Conflict Resolution System (SRC) of the pre-procedural sector. Among the results obtained, the delineation of selection criteria for consensual mechanisms, based on literature and evidence in indicators obtained from research participants, stands out. The guide developed innovates by enabling and guiding the application of criteria when screening cases, based on the analysis of case characteristics combined only with available consensual mechanisms. Furthermore, the product can be used in a self-training instructional way, in simulating situations, to incorporate theoretical knowledge about the concepts included in the criteria. From its implementation, there is a greater probability of meeting the needs of the people involved in the conflict, bringing the broad possibility of a satisfactory, quick and effective response to the case. It is concluded that the results obtained contribute to overcoming choices based on intuition towards a selection of consensual mechanisms parameterized based on theoretical subsidies and consistent scientific evidence. New studies can be developed in a broader context.
Keywords: Política pública judiciária nacional de tratamento adequado dos conflitos de interesses; Mecanismos consensuais de resolução de conflitos; Sistema de resolução de conflitos; National Judicial Public Policy for the Adequate Treatment of Conflicts of Interest; Consensual Conflict; Alternative Dispute Resolution; Conflict Resolution System; CNPQ::CIENCIAS SOCIAIS APLICADAS::DIREITO